2012
DOI: 10.3389/fnint.2012.00067
|View full text |Cite
|
Sign up to set email alerts
|

Capture of visual attention interferes with multisensory speech processing

Abstract: Attending to a conversation in a crowded scene requires selection of relevant information, while ignoring other distracting sensory input, such as speech signals from surrounding people. The neural mechanisms of how distracting stimuli influence the processing of attended speech are not well understood. In this high-density electroencephalography (EEG) study, we investigated how different types of speech and non-speech stimuli influence the processing of attended audiovisual speech. Participants were presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…They also found that the simultaneous occurrence of visual and auditory targets was integrated (i.e., multisensory integration, MSI). The integrated bimodal stimuli can help improve signal salience 8 and attract more attention 9 , 10 . The IOR actually reflect that attention is blocked from returning a previously attended location 11 and facilitates visual exploration by reducing the perceptual salience of a previously explored location 12 .…”
Section: Introductionmentioning
confidence: 99%
“…They also found that the simultaneous occurrence of visual and auditory targets was integrated (i.e., multisensory integration, MSI). The integrated bimodal stimuli can help improve signal salience 8 and attract more attention 9 , 10 . The IOR actually reflect that attention is blocked from returning a previously attended location 11 and facilitates visual exploration by reducing the perceptual salience of a previously explored location 12 .…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, they would gain an automatic processing advantage over unisensory stimuli. In a task that requires a sustained focus of attention on a specific position in the visual field multisensory stimuli may then act as strong distractors (Krause et al, 2012) because they withdraw common processing resources from the task-relevant focus of attention.…”
Section: Introductionmentioning
confidence: 99%
“…Stekelenburg and Vroomen ( 2012 ) also showed that spatial congruity between auditory and visual signals modulates audiovisual interactions reflected in early ERP components, namely, the N1 and P2. Early integration may boost the saliency of the multisensory signals, even when the multisensory signals are irrelevant distractors, causing an attentional shift toward the multisensory distractor, as measured by steady-state visual evoked potentials (SSVEP) in an audiovisual speech task (Krause et al, 2012 ). Instead of using multisensory signals, Töllner et al ( 2012 ) presented separate auditory and visual signals in a dual-task paradigm requiring both auditory and visual discriminations, to investigate influences of task order predictability (TOP) and inter-task onset asynchrony (SOA) on perceptual, and motor processing stages, two stages indexed, respectively, by two EEG components: the Posterior-Contralateral- Negativity (PCN) and the Lateralized-Readiness-Potential (LRP).…”
Section: Electrophysiological and Neuro-imaging Analyses Of Multisensmentioning
confidence: 99%